Comparison of Effectiveness of Antiseptic Wet Wipe Products In Inhibiting Bacterial Growth With Replica Method - Stella Sadheli; Lilih Riniwasih K (INDONESIA NATURAL RESEARCH PHARMACEUTICAL JOURNAL, 2021)
Hand washing is one of various way to maintain hand hygiene to prevent bacteria infections. Along with the development of the pharmaceutical and cosmetics industry appeared wet wipe products that are used as an alternative to handwashing. This study was conducted to determine antimicrobial activity in various samples of antiseptic wet wipe products that are easily obtained in the market in inhibiting the growth of E,coli, S.aureus, and C.albicans bacteria. Testing of antimicrobial properties is done using diffusion method, namely by inoculating the blank disc above so that Muller Hinton Agar that has been bred by bacteria and also replica test, namely by sticking the fingers that have been applied wet wipes on the media agar. The analysis was conducted by measuring the bland zones formed and calculating the number of bacterial colonies growing on the media. As a result, the sample of wet wipes C with isopropyl alcohol content of 70% which has the largest bland zone is 14 mm. In the replica test, only samples of wet wipes A grew bacteria on the media with an average number of 2 colony. In addition, the ANOVA One Way test was also conducted and obtained p > 0.05 which showed there was a significant difference in each treatmentKeywords: Antiseptic wet wipes; Replica method; Antibacteria activity test